Social Engineering Awareness: A Social Science Approach to Cybersecurity Education - Nugraha, Arya Adhi; Nasyuha, Asyahri Hadi (Proceedings International Conference on Education Innovation and Social Science, 2024)
In today's increasingly digital society, individuals and organizations face a growing threat from social engineering attacks that exploit psychological and sociological vulnerabilities. This article investigates the integration of social science principles into cybersecurity education to enhance social engineering awareness. Recognizing the multifaceted nature of these attacks, the article proposes a comprehensive, age-tailored curriculum incorporating insights from psychology, sociology, and anthropology. For children, the curriculum introduces basic concepts of trust and online safety. For teenagers, it focuses on understanding psychological manipulation and promoting responsible online behavior. For adults, it offers advanced training on identifying and countering sophisticated social engineering tactics, fostering a security-conscious culture. The research methodology is based on secondary research, analyzing existing literature and case studies on social engineering and cybersecurity education. By leveraging this data, the article identifies effective educational strategies, such as gamification, scenario-based training, and continuous learning programs. These methods engage learners, enhance their practical skills, and ensure they stay updated on evolving threats. The article also emphasizes the importance of collaboration with social science experts and the use of behavioral analytics and machine learning to personalize training. In conclusion, adopting a social science approach in cybersecurity education significantly improves individuals' ability to recognize and resist social engineering attacks. The proposed curriculum and innovative teaching methods equip learners with the necessary knowledge and skills while fostering a proactive, security-conscious mindset. These efforts ultimately contribute to a more resilient and secure digital environment.